Verifying of Autonomous Domestic Robot in AI using JASON - K V Krishnam Raju, Dr (International Journal of Engineering and Technology, 2018)
The systems that are having self-thinking capability are called autonomous systems. Autonomous systems are used in several modern applications such as the personal, business and industrial systems. The domestic robot is an autonomous system which can be ordered by its owner. The main goal of the domestic robot is to serve drinks to its owner. The functionality is quite simple. The robot goes to the fridge, gets the drink and serves to the owner. The robot also takes care of the health of the owner by limiting the supply of cool drink. The main of this work is to verify whether the domestic robot is meeting its goals or not.Â Â